Medical ventilator system basics : a clinical guide - Lei, Yuan ([Oxford] : Oxford University Press, 2017)
A user-friendly guide to the basic principles and the technical aspects of mechanical ventilation and modern complex ventilator systems.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 27 2017).
Keywords: Respirators (Medical equipment); Respiratory therapy